La atipicidad en la conducta del tipo penal frente a los delitos dolosos. - Arias Garófalo, Lady Fernanda (2022)
The purpose of this research is to study the most relevant dogmatic approaches of today in relation to "atypicality" as a negative element of the theory of crime, a theory that has been collected within the Comprehensive Criminal Organic Code in force since the year 2014, where it has been typified in art. 18 as a criminal offence, to typical, unlawful and guilty conduct to have a legal consequence in the form of a penalty. Therefore, in the face of a certain behavior, a value judgment must be issued aimed at specifying whether there is conduct with criminal relevance; Next, it is necessary to verify if this behavior is described in the criminal code and specify whether or not it adapts to one or more of the descriptions contained in the criminal types, and conclude said judgment with the sustainability of the typicity or the lack of this framework has been called "atypicality" of the conduct according to the case, this process has been called as judgment of typicality within the study of the dogmatic categories of the theory of crime. The principle of legality is the basis of this need for actions or omissions to be included in criminal laws, a guarantee that has been reflected within the due constitutional process enshrined in art. 76 numeral 3 of the Magna Carta. This framework is called criminal typicity. In this sense, the first filter of behavior is typicity, understood as the subsumption of the human, to a criminal type within the catalog of criminal behavior, which the Ecuadorian legislator has foreseen, for which this research opts for the study of the criteria of atypicality in crimes classified as "intentional". The causes of atypicality (or of exclusion of the typicity) are circumstances that, for the material reasons that we will see in the development of this work, will exclude the typicity of the conduct despite the fact that it apparently and formally fits the legal description, and suppose hence the negation of the type. These presuppositions and implications are extensively analyzed in the present work, in order to support the greater adequacy of a material concept of atypicality, based on the theory of objective imputation, such as the theory of the negative elements of the criminal type, although they do not leave of building bridges related to typicity and its negative elements, aspiring to reach a synthesis between the two. The legal consequences for the incorrect application of the legal figure of the atypicality of the conduct would undoubtedly generate arbitrariness on the part of the justice operators, and leading to a maximization of the criminal law that in our country has been established as a mechanism of "ultima ratio" what the present work is relevant in the identification of doctrinal positions of atypicality against intentional crimes for scholars of criminal law, teachers, students of the faculties of jurisprudence; and, justice operators.